Correlation of trans-Lycopene Measurements by the HPLC Method with the Optothermal and Photoacoustic Signals and the Color Readings of Fresh Tomato Homogenates - Bicanic, Dane; Dimitrovski, Darko; Luterotti, Svjetlana; Marković, Ksenija; van Twisk, Charlotte; Buijnsters, Josephus G; Dóka, Otto (Springer Science and Business Media LLC, 2010)
The trans-lycopene content of fresh tomato homogenates was assessed by means of the laser photoacoustic spectroscopy, the laser optothermal window, micro-Raman spectroscopy, and colorimetry; none of these methods require the extraction from the product matrix prior to the analysis. The wet chemistry method (high-performance liquid chromatography) was used as the absolute quantitative method. Analytical figures of merit for all methods were compared statistically; best linear correlation was achieved for the chromaticity index a* and chroma C*.